2022
DOI: 10.3389/fphar.2022.904849
|View full text |Cite
|
Sign up to set email alerts
|

Cuscuta chinensis Lam. Protects Against Light-Induced Retinal Degeneration: Therapeutic Implications for Photoreceptor Degenerative Disorders

Abstract: Cuscuta chinensis Lam. (CCL) is a medicinal herb widely used in traditional Chinese medicine for the treatment of ophthalmic diseases, including age-dependent vision-threatening retinal degenerative disorders that involve irreversible loss of the first-order retinal neurons, photoreceptors. However, evidence is lacking if CCL is pharmacologically active at protecting against loss of photoreceptors and photoreceptor degeneration-associated retinal structural and functional impairment. The current study thus eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Our previous study has demonstrated that Cuscuta chinensis Lam., an herbal medicinal that is conventionally used for the treatment of vision impairment in traditional Chinese medicine, is effective at protecting against oxidative stress-mediated photoreceptor degeneration [ 8 ]. Hyperoside, a flavonol glycoside and the signature chemical constituent of Cuscuta chinensis Lam, is the most abundant flavonoids present in Cuscuta chinensis Lam [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study has demonstrated that Cuscuta chinensis Lam., an herbal medicinal that is conventionally used for the treatment of vision impairment in traditional Chinese medicine, is effective at protecting against oxidative stress-mediated photoreceptor degeneration [ 8 ]. Hyperoside, a flavonol glycoside and the signature chemical constituent of Cuscuta chinensis Lam, is the most abundant flavonoids present in Cuscuta chinensis Lam [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has demonstrated that Cuscuta chinensis Lam., an herbal medicinal that is conventionally used for the treatment of vision impairment in traditional Chinese medicine, is effective at protecting against oxidative stress-mediated photoreceptor degeneration [ 8 ]. Hyperoside, a flavonol glycoside and the signature chemical constituent of Cuscuta chinensis Lam, is the most abundant flavonoids present in Cuscuta chinensis Lam [ 8 ]. Studies performed in experimental models of neurogenerative disorders, for instance, Alzheimer’s disease, have demonstrated that hyperoside protects against neuronal loss in part through suppressing oxidative stress and maintaining the functional integrity of mitochondria [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Image-guided OCT (OCT 2 with Micron IV, Phoenix Research labs, USA) was employed to obtain the full-retinal cross-sectional scans 7 d after the experimental light exposure as previously described (Wu et al 2020 , 2022 ). In brief, intraperitoneal injection of ketamine hydrochloride (82.5 mg/kg bw) and xylazine (8.25 mg/kg bw) was administered to induce anesthesia in the mice, followed by dilation of pupils using 1% tropicamide and OCT imaging.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, the mice were anesthetized with a cocktail of ketamine hydrochloride (82.5 mg/kg bw) and xylazine (8.25 mg/kg bw). After 1% tropicamide-induced dilation of the pupils, ERG recording was proceeded under safe-light conditions (5 lx) using the universal testing and electrophysiological Ganzfeld system (Phoenix Research labs, USA) following the protocols as previously described (Wu et al 2020 ; Wu et al 2022 ). In brief, green light flashes (504 nm) were delivered at the intensity of -2 (0.5 msec duration and 5 s inter-stimulus-interval), -0.8 (1 msec duration and 5 s inter-stimulus-interval), 0.4 (1 msec duration and 10 s inter-stimulus-interval), 1.6 (1 msec duration and 20 s inter-stimulus-interval) and 3.1 (1 msec duration and 60 s inter-stimulus-interval) log cd•s•m − 2 .…”
Section: Methodsmentioning
confidence: 99%